Potensi Jalan dan Taman Bermain Sebagai Ruang Bermain Anak-anak - Gunawan, Michelle Faustine (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2024)
It’s crucial for children’s growth to socialize and play among their peers. To accommodate children’s need to play, some housing developers, including Perumahan Graha Padma, provide playground. However, in Taman Oleander cluster, children barely use the playground as they prefer to play on the street in front of their house instead. It is important to understand the cause of the phenomenon in order to solve the root of the problem. To conduct the research, the data is collected through observation and interview with children who are playing on the street. Then the collected data will be analyzed to interpret the quality of the street and the playground as a place for children’s activities. The playground in Taman Oleander cluster is too far from the houses and too narrow for children to play. On top of that, parents don’t feel safe letting their children to play at their blind spot area. This research can be used as a reference, so in the future when developers creating more playgrounds, children will use them.